2022
DOI: 10.3389/ffgc.2021.787533
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Mangroves: Blue Carbon Hotspots of National and Global Relevance to Natural Climate Solutions

Abstract: Mangroves are known for large carbon stocks and high sequestration rates in biomass and soils, making these intertidal wetlands a cost-effective strategy for some nations to compensate for a portion of their carbon dioxide (CO2) emissions. However, few countries have the national-level inventories required to support the inclusion of mangroves into national carbon credit markets. This is the case for Brazil, home of the second largest mangrove area in the world but lacking an integrated mangrove carbon invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 67 publications
(82 reference statements)
0
18
1
1
Order By: Relevance
“…Amazon mangroves represent 27.9% of the total mangrove area of the country (Ferreira & Lacerda, 2016). These results demonstrate the global importance of Brazilian mangroves as carbon hotspots (Rovai et al, 2022) (Table 1). Mangroves in North Brazil (Amazon mangroves) are part of the world's largest continuous belt of mangroves (760,000 ha) (Souza Filho, 2005).…”
Section: Mangrove Forestsmentioning
confidence: 61%
See 3 more Smart Citations
“…Amazon mangroves represent 27.9% of the total mangrove area of the country (Ferreira & Lacerda, 2016). These results demonstrate the global importance of Brazilian mangroves as carbon hotspots (Rovai et al, 2022) (Table 1). Mangroves in North Brazil (Amazon mangroves) are part of the world's largest continuous belt of mangroves (760,000 ha) (Souza Filho, 2005).…”
Section: Mangrove Forestsmentioning
confidence: 61%
“…However, the overall focus of current BC research on the estimations of total stocks and burial rates (habitat-bound carbon) has overlooked the mobile BC fraction, that is, carbon outwelling (lateral fluxes or horizontal exports of C to the ocean; Santos et al, 2021). Therefore, the sequestration capacity of BCEs can be largely underestimated (Santos et al, 2021;Rovai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in part due to the large extent of the mangrove area and the di culty to access large parts of this region, in particular around the island of Marajó. A recent review of carbon sequestration rates in mangroves of Brazil, suggested that they appear to sequester 15-30% more carbon than other global regions, but it is unknown if this is related to a paucity of data or genuinely re ects the situation in Brazil 10 , particularly considering the fact that only one study was considered for north Brazil, where 77% of the mangroves are located.…”
Section: Introductionmentioning
confidence: 99%